The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1046/j.1472-765x.1998.00258.x
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide sequence of the nifH gene coding for nitrogen reductase in the acetic acid bacterium Acetobacter diazotrophicus

Abstract: The nifH gene sequence of the nitrogen-fixing bacterium Acetobacter diazotrophicus was determined with the use of the polymerase chain reaction and universal degenerate oligonucleotide primers. The gene shows highest pair-wise similarity to the nifH gene of Azospirillum brasilense. The phylogenetic relationships of the nifH gene sequences were compared with those inferred from 16S rRNA gene sequences. Knowledge of the sequence of the nifH gene contributes to the growing database of nifH gene sequences, and wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 1 publication
1
6
0
Order By: Relevance
“…Fifthly, according to Dutta & Gachhui (2007), the major difference between the type strain of Gluconacetobacter kombuchae and related gluconacetobacters was its ability to fix nitrogen. These authors confirmed the presence of the nifH gene in Gluconacetobacter kombuchae by PCR with the degenerate primers 19F and 407R (Franke et al, 1998) and sequencing of the amplified PCR product (Dutta & Gachhui, 2007). In this study, the four strains all generated a PCR product of the same size (~600 bp) using the degenerate primers used by Dutta & Gachhui (2007) (data not shown), indicating the presence of the nifH gene in all of these strains.…”
Section: Strain Numberssupporting
confidence: 66%
“…Fifthly, according to Dutta & Gachhui (2007), the major difference between the type strain of Gluconacetobacter kombuchae and related gluconacetobacters was its ability to fix nitrogen. These authors confirmed the presence of the nifH gene in Gluconacetobacter kombuchae by PCR with the degenerate primers 19F and 407R (Franke et al, 1998) and sequencing of the amplified PCR product (Dutta & Gachhui, 2007). In this study, the four strains all generated a PCR product of the same size (~600 bp) using the degenerate primers used by Dutta & Gachhui (2007) (data not shown), indicating the presence of the nifH gene in all of these strains.…”
Section: Strain Numberssupporting
confidence: 66%
“…1 C and D and SI Appendix, Figs. S1 and S2) and its genome contains a set of genes associated with nitrogen fixation (SI Appendix, Table S1), we were unable to find genes homologous to G. diazotrophicus nifHDK, which form the structural subunits of the nitrogenase complex (47). This either suggests that despite careful handling, very low level nitrogen contamination may have been present, allowing K. rhaeticus to produce cellulose in LGI medium or, alternatively, that K. rhaeticus uses a different set of nitrogenase genes for nitrogen fixation, as alternative nitrogenases have been isolated in other species (48).…”
Section: Discussionmentioning
confidence: 99%
“…Since the PCR primers were designed from the conserved regions of nifD genes, there was no possibility of amplifying other nif genes (Ueda et al 1995). The nif genes only occur in nitrogen-fixing microorganisms and have been used to monitor the presence of these diazotrophs in pure cultures (Franke et al 1998), as well as in plants (Lovell et al 2000).…”
Section: Discussionmentioning
confidence: 99%